Sejarah Perkembangan Gereja Ortodoks Timur Dalam Kerangka Kekaisaran Bizantium - Yurniwati Waruwu; Malik Bambangan (International Forum of Researchers and Lecturers, 2024)
The history of the development of the Eastern Orthodox Church in the Byzantine Empire reflects the close relationship between politics and religion. This study examines how the Eastern Orthodox Church was formed and developed in the context of an empire that dominated the eastern regions of the Christian world. The main issues that arise are the Church's dependence on imperial patronage, internal conflicts such as iconoclasm, and the schism with the Western Church (Schism of 1054), which played a role in the formation of the Eastern Orthodox identity. The purpose of this study is to analyze the development of the Eastern Orthodox Church in the political, cultural, and theological context of the Byzantine Empire. It also explores the imperial influence on the church hierarchy and the evolution of theological teachings, as well as understanding how these dynamics shaped the unique characteristics of the Eastern Orthodox Church. The research method used is qualitative with a historical approach, through the analysis of literature and council documents. Data was drawn from various primary and secondary sources to explore the relationship between the church and the empire. The results show that the Eastern Orthodox Church flourished under Byzantine protection. Internal conflicts such as iconoclasm and external challenges such as the Great Schism affected the historical development of the church. Although the Byzantine Empire collapsed in 1453, its influence remained inherent in the traditions and hierarchy of the Eastern Orthodox Church that persist to this day.